O que resta da pandemia: tecnologia e ecologia no século XXI - Pedro Duarte (O Que Nos Faz Pensar)
Although impactful at the time it occurred, the Covid-19 pandemic, as soon as it subsided as a health crisis, was forgotten. The years of 2020 and 2021, with deaths, illnesses, anxieties, and social isolation, were left behind. However, is it true that the world left after the pandemic has nothing to ponder from it? If we trust what the French philosopher Alain Badiou argued, no. He considered the pandemic a practical problem, requiring little from philosophy. The argument of the following article is that, although Badiou was right to point out the exaggeration of philosophers' projections for good and for bad about the future after the pandemic, his position underestimated that it was not only an empirical health situation, but a historical moment in which the two main concerns of the 21st century crystallized: technology (as pointed out by João Pedro Cachopo), expressed in artificial intelligence; and nature (as pointed out by Bruno Latour), expressed in the Anthropocene.